Determinan Individu Untuk Social Commerce: Kajian Theory of Planned Behavior dan Technology Acceptance Model - Amir Hidayatulloh (Universitas Muhammadiyah Metro, 2019)
The objective of study is to determine the determinants of social media use for social commerce. These factors are associated with theory of planned behavior and technology acceptance model. Population in this study is internet users, while the sample of this study is social media users. Sampling technique using purposive sampling. Criteria used is respondent who have made purchase through social media at least two time the purchase. This research uses SEMPLS analysis tool, in this case that is WarpPLS. Result of this study is perceived usefulness, perceived easy have a positive effect on users attitude towards social media, which ultimately the users attitude towards social media also affect the intention of respondent to make purchase through social media (social commerce). In addition, perceived usefulness is affect the perceived ease use. However, perceived usefulness, subjective norm, and perceived behavior control has no effect on the respondents intention to make purchase through social media.Tujuan penelitian ini adalah untuk mengetahui faktor penentu penggunaan media sosial untuk social commerce. Faktor tersebut dikaitkan dengan theory of planned behavior dan technology acceptance model. Populasi dalam penelitian ini adalah pengguna internet, sedangkan sampel penelitian ini adalah pengguna media sosial. Teknik pengambilan sampel menggunakan purposive sampling. Kriteria yang digunakan yaitu responden yang telah melakukan pembelian melalui media sosial minimal dua kali pembelian. Penelitian ini menggunakan alat analisis SEMPLS, dalam hal ini yaitu WarpPLS. Penelitian ini memperoleh hasil bahwa persepsi kegunaan, kemudahaan penggunaan persepsian berpengaruh positif terhadap sikap pengguna terhadap media sosial, yang akhirnya sikap pengguna terhadap media sosial juga mempengaruhi niat responden untuk melakukan pembelian melalui media sosial. Selain itu, kegunaan persepsian dipengaruhi oleh kemudahaan penggunaan persepsian. Namun, kegunaan persepsian, norma subjektif, dan kontrol perilaku persepsian tidak berpengaruh pada niat responden untuk melakukan pembelian melalui media sosial.